Aquaporin-7: A Dynamic Aquaglyceroporin With Greater Water and Glycerol Permeability Than Its Bacterial Homolog GlpF - Moss, Fraser J.; Mahinthichaichan, Paween; Lodowski, David T.; Kowatz, Thomas; Tajkhorshid, Emad; Engel, Andreas; Boron, Walter F.; Vahedi-Faridi, Ardeschir (Frontiers in Physiology, 2020)
Xenopus oocytes expressing human aquaporin-7 (AQP7) exhibit greater osmotic water permeability and ³H-glycerol uptake vs. those expressing the bacterial glycerol facilitator GlpF. AQP7-expressing oocytes exposed to increasing extracellular [glycerol] under isosmolal conditions exhibit increasing swelling rates, whereas GlpF-expressing oocytes do not swell at all. To understand these differences, we performed X-ray crystallography and molecular-dynamics simulations. The structure reveals AQP7 tetramers containing two monomers with 3 glycerols, and two monomers with 2 glycerols in the pore. In contrast to GlpF, no glycerol is bound at the AQP7 selectivity filter (SF), comprising residues F74, G222, Y223, and R229. The AQP7 SF is resolved in its closed state because F74 blocks the passage of small solutes. Molecular dynamics simulations demonstrate that F74 undergoes large and rapid conformational changes, allowing glycerol molecules to permeate without orientational restriction. The more rigid GlpF imposes orientational constraints on glycerol molecules passing through the SF. Moreover, GlpF-W48 (analogous to AQP7-F74) undergoes rare but long-lasting conformational changes that block the pore to H₂O and glycerol.